Hypostomus caudofasciatus (Teleostei: Loricariidae), a new remarkably colored species from the upper Rio Paraná basin in Brazil - Zawadzki, Cláudio Henrique; Azevedo, Filipe Manoel (Zootaxa, 2024)
Despite being one of the better-surveyed regions in Brazil, the upper Rio Paraná basin still reveals relatively numerous large new species of fish. Here, we present a new uniquely colored species of the highly diverse, armored catfish genus Hypostomus. The new species was mostly found in the Rio Grande basin, plus a single record in the main channel of the Rio Paraná. Hypostomus caudofasciatus n. sp. is remarkable by its large eyes, and it completely differs from congeners by having four longitudinal dark stripes on the flanks and a caudal fin with conspicuous longitudinal dark stripes on a yellow background (unique in Hypostomus).